Production of a monoclonal antibody specific for Citrus Tristeza Virus - (:unkn) unknown (CARFAX PUBLISHING, 2003)
In this work Citrus Tristeza Virus (CTV) was purified from the bark and midrib tissue of infected plants by pulverization of frozen tissue samples in a mortar with extraction buffer, with polyethylene glycol (PEG), and by sucrose gradient centrifugation. In an alternative purification method, CTV was purified by Sephacryl 300 column chromatography after precipitation by PEG. A hybridoma line secreting monoclonal antibody (MAb) highly specific for the CTV was generated by fusion of splenic lymphocytes of immunized BALB/c mice with non-secreting mouse myeloma cells followed by selection in hypoxanthine-aminopterin-thymidine (HAT) medium, and finally, by screening culture fluids for CTV affinity in ELISA. The MAb produced by the CTV-IG8 hybridoma clone was highly specific to CTV and did not react with non-infected citrus plant extracts.
Keywords: Citrus Tristeza Virus; ELISA; immunodiagnosis; monoclonal antibody; COAT PROTEIN; ELISA